Hubungan Status Gizi, Pola Makan, Kebiasaan Minum Kopi dan Tekanan Darah pada Mahasiswa Universitas Airlangga: Association of Nutritional Status, Diet, Coffee Drinking Habits and Blood Pressure of Airlangga University Students - Fuad Zulkarnain Rozaq Sugeha; Trias Mahmudiono; Bella Kartini Rochmania (Amerta Nutrition, 2023)
Background: Non-Communicable Diseases (NCD) is the leading cause of death in the world. One of the causes of death is heart and blood vessel disease. The American Heart Association (AHA) states that one in three people over 20 suffer from hypertension. Hypertension is a risk factor for blood vessels and heart disease. Hypertension risk factors are obesity, a high diet of calories, fat, and salt, a sedentary lifestyle, stress, and lack of exercise. The risk of obesity at a productive age can cause hypertension. UKM members tend to be more active and productive in their daily life than students who do not participate in UKM. Objectives: To analyze the association of nutritional status, diet, coffee drinking habits, and blood pressure of UNAIR Students Methods: The design of this study is a cross-sectional study of 80 student members of UKM UNAIR. Respondents were taken from the population based on the accidental sampling method. The independent variable in this study is blood pressure. The study's dependent variables are nutritional status, diet, and coffee-drinking habits. Data were analyzed using chi-square. Results: There is a correlation between nutritional status (p=0.009), high sodium diet (p=0.022), coffee drinking habits (p=0.046), and blood pressure, and there is no correlation between high-calorie diet (p=0.663) and high-fat diet (p=0.215) and blood pressure. Conclusions: There was a correlation between nutritional status, high sodium diet, and coffee-drinking habits with blood pressure in UNAIR Students.